Pemecahan Masalah Strobe Light Tidak Berkedip Pada ATR 72-500 di Batam Aero Technic - Muhammad Caesar Akbar; Arnold Petrus Legian Legian (Politeknik Penerbangan Makassar, 2023)
When carrying out the Operational test by turning on the strobe light, it is found that the Rear Strobe Light section is not lit. This light that we usually see is flashing white when the plane is in the air. Spotlights are flashing lights that are visible to the ground. Strobe Light is working as an onboard activity activity to be seen by Air Traffic Control (ATC). Strobe Light has a switch to push the lights in the Cockpit on the Overhead Panel. When maintenance was carried out on the ATR 72-500 aircraft, a problem was found, namely Troubleshooting Strobe Light not Flashing ATR 72-500, so the solution was carried out based on the Trouble Shooting Manual (TSM).